Lyophilized and Oven-Dried Manilkara zapota Extracts: Characterization and In Vitro, In Vivo, and In Silico Analyses - María Fernanda Rivas-Gastélum; Patricia Ariadna Galindo-Castillo; Juan Esparza-Sánchez; Miriam Irene Jiménez-Pérez; Yocanxóchitl Perfecto-Avalos; Luis Eduardo Garcia-Amezquita; Diego E. Navarro-López; Edgar R. López-Mena; Eugenio Sánchez-Arreola; Juan Pablo Tamayo-Martínez; Humberto L. Mendoza-Figueroa; María Magdalena Crosby-Galván; et al. (Plants)
In this work, extracts from the pulp, peel, and seed of Manilkara zapota were obtained via lyophilization and oven drying. Bromatological analyses were performed to investigate variabilities in the nutritional content of fruits after nine post-harvest days. The phytochemical content of fruits was assessed by gas chromatography flame ionization detector (GC-FID), and their biological performance was studied using in vitro antibacterial and antioxidant assays (DPPH and ABTS) and in vivo toxicity models. Molecular docking was implemented to evaluate the interaction between polar compounds from chicozapote fruits with receptors involved in the pathogenesis of bacterial strains. Results revealed that water or soluble solids content did not vary after post-harvest. It was demonstrated that lyophilization or oven-drying approaches influenced the insoluble, total dietary fiber and digestible carbohydrates among samples. According to GC-FID analysis, it was observed that lyophilization and oven-drying methods also altered the content of myristic and pentadecanoic acids among the obtained extracts. It was noted that the antibacterial and antioxidant activities of extracts were weak due to their MIC (>1000 μg/mL) and IC50 (>2000 μg/mL) values. Still, the toxicity of extracts was poor against Artemia salina nauplii. In silico evaluation unveiled that polar compounds in M. zapota fruits possess a high binding affinity towards the DNA gyrase B of the cultured strains. This study expands the scientific evidence regarding the influence of distinct extraction methods on the nutritional and nutraceutical content of native fruits and the importance of considering additional approaches to enhance their bioactivities.